The Risk of Nephropathy, Retinopathy, and Leg Amputation in Patients With Diabetes and Hypertension: A Nationwide, Population-Based Retrospective Cohort Study - Yen, Fu-Shun; Wei, James Cheng-Chung; Shih, Ying-Hsiu; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Endocrinology, 2021)
Purpose To compare the risks of chronic kidney disease (CKD), end-stage renal disease (ESRD), sight-threatening retinopathy, and leg amputation between patients with diabetes or hypertension. Methods From January 1, 2000, to December 31, 2015, we identified 28943 matched pairs of patients with diabetes with and without subsequent hypertension, 89102 pairs of patients with hypertension with and without subsequent diabetes, and 145294 pairs of patients with coexisting diabetes and hypertension with a previous history of diabetes or hypertension from Taiwan’s National Health Insurance Research Database. Cox proportional-hazard models were used for calculating the risks of CKD, sight-threatening retinopathy, and leg amputation. Results The mean follow-up time of this study in different cohorts was between 3.59 and 4.28 years. In diabetes patients with vs. without subsequent hypertension, hypertension patients with vs. without subsequent diabetes, and comorbid diabetes and hypertension patients with previous diabetes vs. with previous hypertension, the adjusted HRs (95% CIs) for CKD were 2.77 (2.61-2.94), 1.73 (1.68-1.77), and 1.04 (1.02-1.07); for ESRD were 42.38 (22.62-79.4), 2.76 (2.43-3.13), and 0.72 (0.66-0.79); for sight-threatening retinopathy were 2.07 (1.85-2.3), 3.41 (3.14-3.71), and for leg amputation were 1.51 (1.43-1.58); and 4.74 (3.02-7.43), 6.27(4.72-8.31), and 1.19(1.03-1.38). Conclusions This study demonstrated that both diabetes and hypertension are risk factors for the development of CKD, retinopathy, and amputation. Tracing subsequent diabetes for patients with hypertension, and hypertension for patients with diabetes are important in clinical settings.